An Investigation into the Impact of Decentralization on the Health System of Nepal - Rushton, S.; Pandey, S.; van Teijlingen, E.; Subedi, M.; Balen, J.; Karki, J.; Simkhada, P. (Journal of Manmohan Memorial Institute of Health Sciences, 2021)
This paper introduces our international research project ‘The impact of federalisation on Nepal’s health system: a longitudinal analysis’, which is examining the effects of changing Nepal’s constitution towards a federal republic on its health system. After a short overview of recent changes in the constitution of Nepal, which in turn affects the organisation of the nation’s health system, we offer a short theoretical introduction on the decentralisation of health systems. We briefly outline the WHO (World Health Organization) Health System Building Blocks and some of the issues for policy and practice that have arisen in other countries where similar major system-wide reforms have been implemented. After this, we outline the key research questions and research methods of our study, which involves an international and interdisciplinary team of researchers from Nepal and the UK and will be conducted over a period of three years, from 2020 to 2023.